1980
DOI: 10.1042/cs0580327
|View full text |Cite
|
Sign up to set email alerts
|

Creatinine Metabolism in Chronic Renal Failure

Abstract: 1.Creatinine metabolism was studied in nine patients with severe chronic renal failure who were nevertheless in a nearly steady state with respect to their creatinine pool. Labelled creatinine was injected intravenously and the specific radioactivity of creatinine in urine was measured during the ensuing 5-7 days.2. In each patient, the decline in specific radioactivity with time was a single exponential function after 12 h. The volume of distribution of creatinine averaged 49.1 & 2.8% body weight. The average… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
83
2

Year Published

1984
1984
2013
2013

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 197 publications
(87 citation statements)
references
References 20 publications
(25 reference statements)
2
83
2
Order By: Relevance
“…death, and controlling for urinary creatinine would not abolish the association of higher MDRD GFR with malnutrition. It has been suggested that as much as two thirds of total daily creatinine excretion can occur by extrarenal excretion in patients with advanced renal failure (14). However, our data suggest that 24-h urinary creatinine excretion strongly correlated with malnutrition (Table 3).…”
Section: Discussioncontrasting
confidence: 56%
“…death, and controlling for urinary creatinine would not abolish the association of higher MDRD GFR with malnutrition. It has been suggested that as much as two thirds of total daily creatinine excretion can occur by extrarenal excretion in patients with advanced renal failure (14). However, our data suggest that 24-h urinary creatinine excretion strongly correlated with malnutrition (Table 3).…”
Section: Discussioncontrasting
confidence: 56%
“…Interestingly, a decrease in urinary excretion of guanidinoacetic acid was reported as a sensitive marker of gentamicin nephrotoxicity in rats (Kiyatake et al, 2006;Kiyatake et al, 2004;Takeda et al, 1995) A possible interrelation between the reduced GATM mRNA level and the observed increased plasma concentration of creatinine, which was measured as known marker for renal function in our study, must be discussed as well. There is increasing evidence that increased plasma creatinine levels are associated with increased plasma creatine levels and it was shown that the serum concentration of creatine is increased in many patients with cronic renal failure (Jones and Burnet 1974;Mitch et al, 1980;Wyss and Kaddurah-Daouk, 2000). In rats increased plasma creatine levels resulted in a decrease of GATM mRNA, protein expression and enzymatic activity.…”
Section: Nephrotoxicitymentioning
confidence: 99%
“…This inverse relationship between V D and MaxDP Cr /Day is given by the equation In experimental models, the apparent V D of creatinine is measured to be close to total body water (TBW), with some studies utilizing the strategy above of injecting radiolabeled creatinine and measuring its concentration to infer V D . [15][16][17][18] Although TBW is not routinely measured in the ICU, it can be estimated from existing anthropometric equations, the simplest one being TBW (L) = 0.6 3 weight (kg) for men. For women, 0.5 may be used.…”
Section: Volume Of Distributionmentioning
confidence: 99%